Male infertility: what on earth is going on? Pilot international questionnaire study regarding clinical evaluation and fertility treatment for men - Nkoyenum Pamela Olisa; Lisa Campo-Engelstein; Sarah Martins da Silva (Bioscientifica, 2022)
Infertility is a time-consuming and exhaustive process, which disproportionally affects women. Although concerns have been raised about deficiencies in the clinical evaluation of infertile men, there are currently little published data documenting this. A SurveyMonkey questionnaire was therefore created to capture the current clinical practice of fertility specialists working in in vitro fertilisation clinics. Responses were collected from May to July 2021. A total of 112 clinicians completed the pilot survey with respondents from Europe (n = 49; 43.8%), Africa (n = 39, 34.8%), North America (n = 6; 5.4%), Asia (n = 16; 14.3%), South America (n = 1; 0.9%) and Australasia (n = 1; 0.9%). Forty-one percent of fertility specialists (45/110) reported taking only a brief medical history and 24% reported that they never routinely examined infertile male patients. Fifty-four percent of fertility specialists also reported issues getting men to undertake diagnostic semen analysis. Treatment for male infertility spanned assisted reproductive technology (ART), with themes of individualised medicine influencing treatment recommendations. Of the clinicians, 48.2% clinicians reported using empirical medical therapy for unexplained male infertility. Notably, 3.6% respondents recommended testosterone treatment, despite the likely negative impact on spermatogenesis. However, high levels of opportunistic general health advice were reported, including discussion of life exposures thought to be important for male reproductive health. This study adds novel evidence and highlights current deficiencies in clinical practice relating to male infertility. Evaluation of the infertile male using simple medical tools (detailed history taking and clinical examination) has the potential to identify treatable or reversible conditions and should be an immediate focus for education and improvement in reproductive medicine. Investment in research and development is much needed in the field of andrology to develop effective non- ART treatment options for male infertility.